Argument Structure in Essays Written by Class VIII Students of SMP Muhammadiyah 1 Kartasura - Markhamah, Markhamah; Wulandari, Linda Septi (Universitas Hamzanwadi, 2021)
The purpose of this study was to analyze the argument structure of the exposition text in the essays written by students. This research is a type of qualitative research with a qualitative descriptive research. The data in this study is the structure of the argument in the exposition text written by students of SMP. The data analysis method is the structural analysis and content analysis method. The results of this study indicate that there is no exposition text written by students with a complete structure. Argument structure contained in the student's exposition includes the qualifier structure (qualification) in 3 texts, backing (support) is found in 3 texts, claims (claims) are in 1 text, data (data) is in 3 texts.Kata kunci: Argument structure, short story, exposition text